(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Thiazolidinedione (1) was used as a key intermediate for the synthesis of many therapeutic anti-diabetic molecule. Thus, Thiazolidinedione (1) was refluxed with aromatic aldehydes and phenol derivatives to afforded aryldine derivative (3). Moreover, the stereochemistry for compound 3 was discussed using Hartree-Fock theory geometries, and have been optimized at HF with 6-311G level of theory. The HOMO-LUMO energy gap of studied systems has been discussed. The molecular docking simulations into the active site of ALR2 were performed, and showed that, the compound 3 more suitable inhibitor against ALR2 and can used as anti- diabetic drug.